Effect of corn gluten and its hydrolysate consumptions on weight reduction in rats fed a high-fat diet - Kim, Joohee (The Korean Nutrition Society and The Korean Society of Community Nutrition, 2009)
This study examined the effects of corn gluten (CG) and its hydrolysate consumptions on weight reduction in rats fed a high-fat diet. Eight-month-old male Sprague-Dawley rats (n=40) were fed a high-fat diet (40% calorie as fat) for 4 weeks. They were then randomly divided into four groups and fed the isocaloric diets with different protein sources for 8 weeks. The protein sources were casein (control group), intact CG (CG group), CG hydrolysate A (CGHA group, 30% of protein as peptides and 70% as free amino acids) and CG hydrolysate P (CGHP group, 93% of protein as peptides and 7% as free amino acids). Body weight gain, adipose tissue weights, nitrogen balance, absorptions of energy, protein and fat, lipid profiles in plasma, liver and feces and hepatic activities of carnitine palmitoyl transferase (CPT), fatty acid synthase (FAS), malic enzyme (ME) and glucose-6-phosphate dehydrogenase (G6PDH) were assessed. The CGHA diet had the highest amount of BCAAs, especially leucine, and most of them existed as free amino acid forms. The CGHA group showed significant weight reduction and negative nitrogen balance. Protein absorption and apparent protein digestibility in the CGHA group were significantly lower than those in other groups. Adipose tissue weights were the lowest in the CGHA group. Activity of CPT tended to be higher in the CGHA group than in other groups and those of FAS, ME and G6PDH were significantly lower in the CGHA group than in other groups. In conclusion, the CGHA diet which had relatively high amounts of free amino acids and BCAAs, especially leucine, had a weight reduction effect by lowering adipose tissue weight and the activities of FAS, ME and G6PDH in experimental animals, but it seemed to be a negative result induced by lowering protein absorption, increasing urinary nitrogen excretion and protein catabolism.